Auditoría de gestión a la empresa “UTIP S.A.” Unidad de Transporte Interinstitucional Pichincha, cantón La Maná, provincia de Cotopaxi período 2022. - Casanova Giler, Kenia Rosely (2024)
Considering that the management audit is a fundamental process to ensure the long-term success of a company by identifying areas for improvement, the general objective of this research was to conduct a management audit of the company "UTIP S.A." Unidad de Transporte Interinstitucional Pichincha during the period 2022, to improve the quality of service of this company. For this purpose, descriptive was reviewed, bibliographic research for the collection of theoretical information that supported the bases of the performance audit, and field research was also used for the development of the situational diagnosis, evaluation of internal control, and the various phases of the performance audit. The following methods were also used: analytical, inductive, deductive, and the techniques of direct observation, interviews, and surveys to collect the primary information that allowed the detection of the findings. Through the situational diagnosis, it was possible to identify the need to strengthen knowledge in this regard, to improve its performance and capacity for evaluation and internal control. Training on quality service is carried out sporadically and does not respond to specific objectives. The findings detected in the audit were eleven among missions, vision, and values weren't defined in a documented and formal way, the lack of a training plan for employees, low level of information security, lack of documented actions to improve the quality of service, not developing management audits, not applying efficiency indicators and failure to submit the documentation requested by the Superintendence of companies to which a manual with suggestions for improving the quality of the "UTIP S.A." was proposed.